Nearly the New World: the British West Indies and the flight from Nazism, 1933-1945 - Newman, Joanna (Berghahn, 2019)
The contextual drivers : the British West Indies, the colonial office and Jewish refugee organizations -- Jews seeking refuge, 1933-1938 -- Panic migration : the British West Indies and the refugee crisis of 1938-39 -- Boat people -- Internment, camps and missed opportunities.